Cytotoxicity of Mangrove Leaves (Rhizophora) Ethanolic Extract on Cancer Cells - Haryoto Saroyo; Nur Fajariyah Maulidah Saputri (Journal of Nutraceuticals and Herbal Medicine, 2021)
Cancer is a disease that can attack any part of the body when the abnormal cells begin to grow  uncontrollably beyond the limit, then attack the connected parts of the body and  spread to other organs. The mangrove (Rhizophora) is a herbal plant that can be used as a treatment for various diseases, one of which is cancer. The mangrove (Rhizophora) plant contains phytochemicals  ranging from fruit, seeds, leaves and roots. This review article aims to examine the cytotoxicity effects of mangrove (Rhizophora)  plants on cancer cells. The library sources in this article review use the Google Scholar and PubMed databases. The inclusion criteria used were articles containing the cytotoxic test of mangrove (Rhizophora) with the last 10 years of publication (2011-2020), original research, there were results of anticancer activity in the form of IC50 and research using   mangrove (Rhizophora).  plant extracts. The exclusion criteria used were articles that did not contain a full text, used plants with different genus, did not have an IC50 value and were not original research. From the journals that have been analyzed, it can be said that the extract of the mangrove (Rhizophora) plant can be developed for cancer treatment. The mangrove (Rhizophora) plant has cytotoxic activity because it contains active compounds in the form of phenolic, flavonoids and terpenoids. Based on the results of the cytotoxic test of mangrove (Rhizophora) extract, the plant parts that have the strongest cytotoxic effect are fruit.